Comparative MiRNA Expressional Profiles and Molecular Networks in Human Small Bowel Tissues of Necrotizing Enterocolitis and Spontaneous Intestinal Perforation. - Pak Cheung Ng; Kathy Yuen Yee Chan; Kam Tong Leung; Yuk Him Tam; Terence Ping Yuen Ma; Hugh Simon Lam; Hon Ming Cheung; Kim Hung Lee; Ka Fai To; Karen Li (PLoS ONE, 2015)
Necrotizing enterocolitis (NEC) and spontaneous intestinal perforation (SIP) are acute intestinal conditions which could result in mortality and severe morbidity in preterm infants. Our objective was to identify dysregulated micro-RNAs (miRNAs) in small bowel tissues of NEC and SIP, and their possible roles in disease pathophysiology.We performed differential miRNA arrays on tissues of NEC (n = 4), SIP (n = 4) and surgical-control (Surg-CTL; n = 4), and validated target miRNAs by qPCR (n = 10 each group). The association of target miRNAs with 52 dysregulated mRNAs was investigated by bioinformatics on functional and base-pair sequence algorithms, and correlation in same tissue samples.We presented the first miRNA profiles of NEC, SIP and Surg-CTL intestinal tissues in preterm infants. Of 28 validated miRNAs, 21 were significantly different between NEC or SIP and Surg-CTL. Limited overlapping in the aberrant expression of miRNAs between NEC and SIP indicated their distinct molecular mechanisms. A proposed network of dysregulated miRNA/mRNA pairs in NEC suggested interaction at bacterial receptor TLR4 (miR-31, miR-451, miR-203, miR-4793-3p), mediated via key transcription factors NFKB2 (miR-203), AP-1/FOSL1 (miR-194-3p), FOXA1 (miR-21-3p, miR-431 and miR-1290) and HIF1A (miR-31), and extended downstream to pathways of angiogenesis, arginine metabolism, cell adhesion and chemotaxis, extracellular matrix remodeling, hypoxia/oxidative stress, inflammation and muscle contraction. In contrast, upregulation of miR-451 and miR-223 in SIP suggested modulation of G-protein-mediated muscle contraction.The robust response of miRNA dysregulation in NEC and SIP, and concerted involvement of specific miRNAs in the molecular networks indicated their crucial roles in mucosa integrity and disease pathophysiology.